2009
DOI: 10.1093/molehr/gap096
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of phase I and phase II detoxification genes with recurrent miscarriages among North Indian women

Abstract: Allelic variants of the detoxification genes that have impaired biotransformation functions may increase susceptibility to reproductive toxicity leading to endometriosis, recurrent miscarriage (RM) or poor pregnancy outcome. In the present study, we have investigated CYP1A1, CYP2D6, GSTT1, GSTP1 and GSTM1, which are involved in the phase I and phase II detoxification systems, in relation to their role in the etiology of unexplained RMs. In a case-control study, we have investigated 200 females with RM and 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…After the full-text evaluation, five articles were excluded with reasons for no available data (n = 1) [11], irrelevance to endometriosis (n = 1) [12], duplicate publications (n = 3) [13][14][15]. An article providing data for two different subgroups (Caucasian and Asian) was counted as two separate studies [6].…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…After the full-text evaluation, five articles were excluded with reasons for no available data (n = 1) [11], irrelevance to endometriosis (n = 1) [12], duplicate publications (n = 3) [13][14][15]. An article providing data for two different subgroups (Caucasian and Asian) was counted as two separate studies [6].…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…This suggests that GSTP1 may be the most important GST in the pathogenesis of endometrial hyperplasia. For this reason, several studies have been conducted to evaluate the association of GSTP1-313 A > G polymorphism with endometrial carcinoma risk [15][16][17][18][19][20][21][22], but there were no previous results evaluating the association between this polymorphism and endometrial hyperplasia. Therefore, the aim of our study is to derive a more precise estimation of the association between GSTP1-313 A > G (Ile105Val) polymorphism and EH susceptibility among Egyptian women.…”
Section: Introductionmentioning
confidence: 99%
“…GSTs are divided into three families: cytosolic, mitochondrial, and the membrane-associated proteins in eicosanoid and glutathione metabolism proteins, among them, the cytosolic subfamily is by far the most abundant one [7]. Numbers of studies have suggested that the genetic polymorphism of cytosolic GST genes was associated with the risk of RSA [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%